2003
DOI: 10.1051/0004-6361:20021861
|View full text |Cite
|
Sign up to set email alerts
|

R-band imaging of the host galaxies of RGB BL Lacertae objects

Abstract: Abstract. We present optical R-band images of 100 BL Lacertae objects in the ROSAT-Green Bank (RGB) sample obtained at the Nordic Optical Telescope (NOT). For 62 objects we could not find any previously published images in the literature, of these 35 are new BL Lacs discovered during the RGB BL Lac survey. We were able to resolve the host galaxy in 62% of the objects. We analyze the host galaxies using a two-dimensional fitting procedure and tabulate the best-fit core magnitude and host galaxy parameters (magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
124
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 98 publications
(140 citation statements)
references
References 64 publications
12
124
0
4
Order By: Relevance
“…In all 19 cases where our simulations showed the host galaxy type to be well determined the bulge model was preferred. This result is in line with previous BL Lac host galaxy imaging surveys (e.g., Urry et al 2000;Nilsson et al 2003), which show that BL Lacs are almost exclusively found in ellipticals. Given this result we use the bulge fit results for all targets from this point on.…”
Section: Host Galaxiessupporting
confidence: 92%
See 1 more Smart Citation
“…In all 19 cases where our simulations showed the host galaxy type to be well determined the bulge model was preferred. This result is in line with previous BL Lac host galaxy imaging surveys (e.g., Urry et al 2000;Nilsson et al 2003), which show that BL Lacs are almost exclusively found in ellipticals. Given this result we use the bulge fit results for all targets from this point on.…”
Section: Host Galaxiessupporting
confidence: 92%
“…Heidt et al 1999;Nilsson et al 2003Nilsson et al , 2007. A more detailed description of the fitting procedure can be found in Nilsson et al (1999), here we briefly describe the main features of the program and its application to present data.…”
Section: Host Galaxiesmentioning
confidence: 99%
“…Piranomonte et al (2007) derived a lower limit z > 0.193 based on the absence of host galaxy features in the spectrum. In the only imaging attempt so far, Nilsson et al (2003) did not detect the host galaxy in a 1200 s R-band exposure.…”
Section: Introductionmentioning
confidence: 89%
“…This object shows a featureless spectrum and its host galaxy can be resolved in the images (Abraham et al 1991;Falomo 1996), but it is rather faint compared to the AGN. Nilsson et al (2003) suggest a host magnitude of R = 18.55 mag and r eff = 1.3 arcsec. Carangelo et al (2003) suggest a redshift z = 0.266 ± 0.001 based on the identification of two faint emission lines.…”
Section: Resultsmentioning
confidence: 90%